2012
DOI: 10.1089/scd.2011.0516
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of the Antioxidant Enzyme SOD3 Occur Upon Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells In Vitro

Abstract: The discovery that mesenchymal stem cells (MSCs) secrete SOD3 may help explain studies in which MSCs have direct antioxidant activities both in vivo and in vitro. SOD3 is an antioxidant enzyme that dismutes toxic free radicals produced during inflammatory processes. Therefore, MSC production and secretion of active and therapeutically significant levels of SOD3 would further support the use of MSCs as a cellular based antioxidant therapy. The aim of this study was therefore to investigate in vitro if MSC diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…The reduction in glutathione (Fig. A) during early MSCs chondrogenesis suggests that increases in intracellular ROS are at least in part due to downregulation of endogenous antioxidants, which has been previously reported for MSCs chondrogenesis and superoxide dismutase . Moderate levels of ROS can act as important secondary messengers that influence stem cell survival, migration, and differentiation .…”
Section: Discussionsupporting
confidence: 54%
“…The reduction in glutathione (Fig. A) during early MSCs chondrogenesis suggests that increases in intracellular ROS are at least in part due to downregulation of endogenous antioxidants, which has been previously reported for MSCs chondrogenesis and superoxide dismutase . Moderate levels of ROS can act as important secondary messengers that influence stem cell survival, migration, and differentiation .…”
Section: Discussionsupporting
confidence: 54%
“…There are three metal containing isoforms of SOD found in different cellular compartments [38]: SOD1 (copper-zinc SOD) is in the cytoplasm, nucleus and plasma membrane; SOD2 (manganese SOD) is mainly in mitochondria [5]; and SOD3 (copper-zinc SOD) is unique in scavenging superoxide in the extracellular compartment, dismutating superoxides generated during the inflammatory cascade [39]. Bone marrow-derived human mesenchymal stem cells (MSC) specifically secrete SOD3 directly promoting cell survival by reducing toxic ROS [40].…”
Section: Cellular Antioxidant Systemsmentioning
confidence: 99%
“…Bone marrow-derived human mesenchymal stem cells (MSC) specifically secrete SOD3 directly promoting cell survival by reducing toxic ROS [40]. MSC differentiation through the adipogenic, chondrogenic, and osteogenic lineages influences the expression of SOD3 [39]. SOD operates in conjunction with catalase to maintain hydrogen peroxide levels resulting from SOD catalysis.…”
Section: Cellular Antioxidant Systemsmentioning
confidence: 99%
“…It has previously been shown that SAMs can have a protective effect on metal surfaces, helping to slow down oxidation, which may help to protect against cell‐induced degradation of the Au. Additionally, in contrast to many other cell types, mesenchymal stem cells are known to inhibit oxidative processes, secreting the enzyme superoxide dismutase 3 (SOD3), an antioxidant enzyme that catalyzes the reduction of superoxides . It is also possible that the nonproliferative state of the HMSCs induced to enable appropriate cell counting in these studies affects the production of SAM‐degrading factors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in contrast to many other cell types, mesenchymal stem cells are known to inhibit oxidative processes, secreting the enzyme superoxide dismutase 3 (SOD3), an antioxidant enzyme that catalyzes the reduction of superoxides. 65 It is also possible that the nonproliferative state of the HMSCs induced to enable appropriate cell counting in these studies affects the production of SAM-degrading factors. HMSCs on 4 and 10 nm Au began to migrate away from their initial confinement to the originally SAM coated regions at 5 days with 53.0% 6 11.7% and 2.5% 6 0.0% of cells migrating, respectively.…”
Section: Time-dependent Cell Migration On Alkanethiol Sams As a Functmentioning
confidence: 99%